Measuring The Trust of Corporate Waqifs to Donate Cash Waqf to The Indonesian Waqf Board - Dewi, Sri Yanita; Ismal, Rifki; Tanjung, Hendri (International Journal of Economics (IJEC), 2024)
This research aims to measure the trust of institutional waqif to distribute waqf to waqf institutions, in this case, the Indonesian Waqf Board (BWI), in the form of an index referring to the Waqf Core Principles (WCP). This study measures the trust of institutional waqif to distribute cash waqf through BWI based on WCP using an index (100 scale), which composed of individual index of waqf supervision, nazhir governance, risk management, sharia governance, and the overall trust index. The institutional waqif trust index to distribute waqf to BWI is “trust” (53.36). Based on components: a. waqf supervision index is trust (13.49), b. nazhir governance index is trust (3.18), risk management index is trust (25.24), and sharia governance index is trust (11.45). Increasing the trust of institutional waqf in BWI can be done through the improvement and management of waqf from large-scale institutional waqf, preparation of BWI communication strategies which include implementation of waqf and policies, and transfer of knowledge from waqf institutions to institutional waqif. This thesis will provide additional knowledge to academics regarding the potential of institutional waqif and the implementation of WCP in Indonesia. In addition, this research practically provides recommendations for regulators, waqf institutions, and related parties to optimize the collection, management, and supervision of waqf in Indonesia. Based on the author's knowledge, this is the first paper to measure the trustworthiness of institutional waqif. This paper is expected to provide novelty regarding the level of trust of a institutional waqif to a waqf institution in the form of an index.